Pengaruh Regulasi Emosi Single Mother terhadap Penerimaan Diri pada Anak Se-Kecamatan Rumbai Kota Pekanbaru - Rany Handri Yanti; Ria Novianti; Enda Puspitasari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Abstract:. This research aims to determine the level of influence of the emotional regulation of single mother to the acceptance of children in the sub-district Rumbai Pekanbaru City. The samples in this study were the son and single mother of the sub-district Rumbai Pekanbaru which amounted to 22 children and mothers. The method used is the correlation of Chi Square to see the influence between the regulatory variables of single mother's emotions towards child acceptance. The data collection techniques used are questionnaires in the form of Likert scales. Data analysis techniques using scale trials and statistical method analysis. Visible from the overall amount of the emotional Regulation indicator single mother can be concluded that the emotional regulation is in good category with a percentage of 71.83%, while on the child's self-acceptance indicators are in a very good category with Percentage of 81.31%. From the results of the test, the results of Chi Square were obtained a probability figure of 0.044 which is 0.044 < 0.05, then Ho rejected and Ha accepted. This means that there is a significant influence between single mother's emotional regulation of child acceptance. Keywords: Single mother, Emotional Regulation, Child, Self-Acceptance Abstrak. Penelitian ini bertujuan untuk mengetahui tingkat pengaruh regulasi emosi single mother terhadap penerimaan diri pada anak se-Kecamatan Rumbai kota Pekanbaru. Adapun sampel dalam penelitian ini adalah anak dan ibu tunggal se-kecamatan Rumbai kota Pekanbaru yang berjumlah 22 anak dan ibu. Metode yang digunakan yaitu korelasi Chi Square untuk melihat pengaruh antara variabel regulasi emosi single mother terhadap penerimaan diri anak. Teknik pengumpulan data yang digunakan yaitu kuesioner dalam bentuk skala Likert. Teknik analisa data menggunakan uji coba skala dan analisa metode statistik. Terlihat dari jumlah keseluruhan indikator regulasi emosi single mother dapat disimpulkan bahwa regulasi emosi berada dalam kategori baik dengan persentase 71,83 %, sedangkan pada indikator penerimaan diri anak berada dalam kategori sangat baik dengan persentase 81,31 %. Dari hasil uji Chi Square diketahuui hasil analisis diperoleh angka probabilitas sebesar 0,044 dimana 0,044 < 0,05, maka Ho ditolak dan Ha diterima. Artinya terdapat pengaruh yang signifikan antara regulasi emosi single mother terhadap penerimaan diri anak. Kata Kunci: Single Mother, Regulasi Emosi, Anak, Penerimaan Diri